Peran Citra Merek Memediasi Pengaruh Kualitas Produk Terhadap Keputusan Pembelian Pada Pembeli Keripik Tempe Rohani Di Kota Malang - Angraeni, Novi; Kurriwati, Nirma (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
Rapid developments in the snack food industry, especially tempeh chips products, have been seen in recent years. Increasingly tight business competition makes brand image and product quality the main factors influencing consumer purchasing decisions. Tight competition in the tempeh chips market, especially in Malang City, is the main challenge that has caused a decline in sales. Therefore, this research aims to examine the influence of product quality and brand image on purchasing decisions for Rohani Tempe Chips in Malang. This research uses an inferential statistical approach with 96 respondents selected through a purposive sampling technique, focusing on consumers who have purchased Rohani Tempe Chips in Malang City. Data was collected through questionnaires and analyzed using path analysis. The research results show that: Product quality has a positive and significant effect on purchasing decisions, Brand image has a positive and significant effect on purchasing decisions, Product quality has a positive and significant effect on brand image, Product quality has a positive and significant effect on purchasing decisions for Rohani Tempe Chips in Malang through brand image.